Abortion Due to Rape in A Juridical Perspective and Human Rights - Ila Ria Alfi; Gunarto Gunarto (Universitas Islam Sultan Agung, 2020)
The problem of abortion due to rape is a social reality that is becoming increasingly prevalent in society. It is not uncommon in Indonesia that abortions are performed not because of health or age factors but because of shame and self-esteem. The purpose of this study was to determine and analyze the regulations regarding abortion due to rape based on Act No. 36 of 2009 concerning Health and a legal review of acts of abortion due to rape based on Act No. 36 of 2009 concerning Health and its relation to human rights. This study uses a juridical-normative approach and data collection techniques are carried out by collecting secondary data. The results of this study indicate that abortion cannot be done arbitrarily, there must be reasons and conditions that are met in accordance with statutory qualifications. Sanctions for violating these provisions can be subject to penalties. Judging from juridically, Act No. 36 Of 2009 concerning Health, Article 75 in particular paragraph (2) provides room for abortion for victims of rape. The article states that a pregnancy resulting from rape which can cause psychological trauma to the rape victim can be subjected to an abortion. In Article 9 of Act No. 39 Of 1999 concerning Human Rights paragraph (1) it is emphasized that everyone has the right to live, and to maintain life and to improve his standard of living. Human rights are basic rights that humans have since they were born.